The composition of old age homes in South Africa in relation to the residents and nursing personnel - A. Perold (AOSIS, 2000)
This research project is the first phase of a larger study aimed at describing and exploring the cost-effective utilisation of nursing personnel in old age homes in South Africa. The aim in the first phase was to describe the composition of the residents and nursing personnel of old age homes in South Africa. An exploratory and descriptive survey was conducted and the data was collected by means of a questionnaire. The questionnaire also included data on the financial implications of utilising professional nursing personnel to manage the care of the frail residents/older persons in old age homes in South Africa. The questionnaires were mailed to 612 old age homes published in the Hospital and Nursing Yearbook of 1997 (100% sample). A total of 145 (23.69%) questionnaires were returned and included in the descriptive data analysis. The residents are mainly female (77%), older than 85 years of age, belong to the white race group (83,74%) and are highly dependent on nursing care and supervision (69,7%). Old age homes are mainly managed/ controlled by welfare organisations and lay health care workers are utilised to a large extent (42,22% of the nursing workforce) to render nursing care to the frail residents. The cost-effective utilisation of nursing personnel (registered and enrolled), as well as the utilisation of lay health workers in old age homes, needs to be critically examined.